Catheterization of the urethra in female pigs. (October 2015) - Musk, GC; Zwierzchoniewska, M; He, B
Female pigs are commonly utilized as an animal model for biomedical research and require urethral catheterization. Sixteen pigs were anaesthetized for research purposes and required the placement of a urethral catheter. Post-mortem examination of the vaginas revealed the urethral opening to be consistently halfway from the mucocutaneous junction of the vulva to the cervix. A shallow diverticulum was also observed on the ventral floor of the urethral opening. To optimize conditions for success the pig should be carefully positioned supine, a vaginal speculum and light source should be used, the pig should be adequately anaesthetized, and the anatomy of the vagina should be reviewed.